Gender differences in adverse outcomes after contemporary percutaneous coronary intervention: An analysis from the Blue Cross Blue Shield of Michigan Cardiovascular Consortium (BMC2) percutaneous coronary intervention registry - Duvernoy, Claire S.; Smith, Dean E.; Manohar, Prerana; Schaefer, Ann; Kline-Rogers, Eva; Share, David; McNamara, Richard; Gurm, Hitinder S.; Moscucci, Mauro (The American heart journal, 2010)
Prior studies have shown a relationship between female gender and adverse outcomes after percutaneous coronary interventions (PCIs). Whether this relationship still exists with contemporary PCI remains to be determined. We evaluated gender differences in clinical outcomes in a large registry of contemporary PCI. Data were prospectively collected from 22,725 consecutive PCIs in a multicenter regional consortium (Blue Cross Blue Shield of Michigan Cardiovascular Consortium) between January 2002 and December 2003. The primary end point was in-hospital all-cause mortality; other clinical outcomes evaluated included in-hospital death, vascular complications, transfusion, postprocedure myocardial infarction, stroke, and a combined major cardiovascular adverse event (MACE) end point including myocardial infarction, death, stroke, emergency coronary artery bypass grafting, and repeated PCI at the same site. Independent predictors of adverse outcomes were identified using multivariate logistic regression analysis. Compared with men, women were older, had a higher prevalence of comorbidities, and had a significantly higher frequency of adverse outcomes after PCI. After adjustment for baseline demographics, comorbidities, clinical presentation, and lesion characteristics, female gender was associated with an increased risk of in-hospital death, vascular complication, blood transfusion, stroke, and MACE. The relationship between female gender and increased risk of death and MACE was no longer present after further adjustment for kidney function and low body surface area. Differences in mortality rates between men and women no longer exist after PCI. However, our data suggest that technological advancements have not completely offset the relationship between gender and adverse outcomes after PCI.